Patterns, predictors and outcomes of patient transfer in public sector chronic primary care services - Odayar, Jasantha (Department of Public Health and Family Medicine, 2025)
Background: To maintain long-term care, patients with chronic conditions may require transfers between health facilities, jeopardising continuity of care. High levels of geographic mobility in low-and middle-income countries mean that patients may require transfers between primary health care (PHC) facilities. In addition, with decentralisation of chronic care services in many settings there are increasing numbers of PHC facilities between which patients can transfer. However, research on transfers between PHC facilities is limited. This thesis investigated transfers between PHC facilities of stable patients with chronic conditions in South Africa using HIV and diabetes as exemplars. Methods: First, national guidelines were reviewed for recommendations regarding transfers of people living with HIV (PLH). Second, routinely collected data from across the Western Cape were used to determine transfer incidence and outcomes among PLH and people living with diabetes (PLD). Third, at a PHC facility in Cape Town, medical records of PLH transferring in from any PHC facility in the province were reviewed to compare features of silent (health facility not informed of transfer, transfer letter not obtained) and official (health facility informed, transfer letter obtained) transfers. Fourth, in a trial of antiretroviral therapy (ART) delivery strategies among postpartum women, data were obtained from questionnaires (demographics and travel history) and in-depth interviews exploring barriers to transfer. Findings: Recommendations regarding management of transfers between PHC facilities were limited, particularly for silent transfers. Transfers between PHC facilities occurred frequently among PLH and PLD and were associated with viraemia and raised HbA1c results respectively. Among PLH transferring into a PHC facility, 52% had interrupted ART and 30% had clinical concerns; these percentages were higher among silent than official transfers. Among postpartum women, poor relationships with healthcare providers led to silent transfers; barriers to successful transfer included fear of community stigma and limited knowledge of transfer options and processes including for mobile women. Conclusions: Considering the volume and outcomes of transfers among PLH and PLD, routine monitoring and reporting of the number of transfers and transfer outcomes should be considered. Research on interventions to improve transfer outcomes and on transfers among people with other chronic conditions is warranted